Three-Dimensional Analysis of Definitive Secondary Unilateral Cleft Rhinoplasty Using Cartilage Graft - Hantawornchaikit T. (2023)
Objective: Three-dimensional assessment of nasal morphology in patients with unilateral cleft lip nose treated by cartilage graft augmentation. Design: Retrospective study. Patients and Intervention: Thirteen patients with unilateral cleft lip nose underwent definitive secondary rhinoplasty and postsurgical changes were examined using a three-dimensional (3D) laser scan. Main Outcome Measure: Nasal dorsum length, nasal tip, alar width, and alar base width in frontal view; nasion depth, nasal tip projection, nasal dorsal angle, and nasal tip angle in lateral view; nostril width, nostril height, and nasal tip height in basal view were measured at preoperative (T1: within 6 months), short follow-up (T2: 2-10 weeks), and long follow-up (T3: 9-14 months). Results: A significant change in alar width, alar base width, nostril width, and nostril height at the cleft side, nasal dorsum length, nasion depth, nasal tip projection, and nasal tip height was observed from T1 to T3 follow-up after rhinoplasty (P <.05), whereas the nostril height at the noncleft side was also significantly increased at T2 follow-up but the mean change in height relapsed at T3 follow-up. Alar width, alar base width, and nostril width at the noncleft side, and nasal tip angle did not change significantly after surgery at any follow-up period. Conclusions: 3D imaging evaluation after secondary cleft rhinoplasty demonstrated improved functional and aesthetic outcomes using a septal or conchal graft.